Single nucleotide polymorphisms in noncoding regions of Rad51C do not change the risk of unselected breast cancer but they modulate the level of oxidative stress and the DNA damage characteristics: a case-control study. - Peter Gresner; Jolanta Gromadzinska; Ewa Jablonska; Maciej Stepnik; Oscar Zambrano Quispe; Ewa Twardowska; Wojciech Wasowicz (PLoS ONE, 2014)
Deleterious and missense mutations of RAD51C have recently been suggested to modulate the individual susceptibility to hereditary breast and ovarian cancer and unselected ovarian cancer, but not unselected breast cancer (BrC). We enrolled 132 unselected BrC females and 189 cancer-free female subjects to investigate whether common single nucleotide polymorphisms (SNPs) in non-coding regions of RAD51C modulate the risk of BrC, and whether they affect the level of oxidative stress and the extent/characteristics of DNA damage. Neither SNPs nor reconstructed haplotypes were found to significantly affect the unselected BrC risk. Contrary to this, carriers of rs12946522, rs16943176, rs12946397 and rs17222691 rare-alleles were found to present significantly increased level of blood plasma TBARS compared to respective wild-type homozygotes (p<0.05). Furthermore, these carriers showed significantly decreased fraction of oxidatively generated DNA damage (34% of total damaged DNA) in favor of DNA strand breakage, with no effect on total DNA damage, unlike respective wild-types, among which more evenly distributed proportions between oxidatively damaged DNA (48% of total DNA damage) and DNA strand breakage was found (p<0.0005 for the difference). Such effects were found among both the BrC cases and healthy subjects, indicating that they cannot be assumed as causal factors contributing to BrC development.